(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Bacillus subtilis and other Bacilli have long been used in the field of agriculture as a biocontrol reagent to protect plants against soil-borne plant pathogens. Evaluation the efficacy of bio-agents, application as foliar spray against vegetables foliar diseases incidence was carried out in greenhouse conditions. The tested Russian bio agents Bacillus subtilis-26D, and Bacillus subtilis-M-22 were evaluated. The recorded foliar diseases, i.e. Powdery mildew, Angular spots of Cucumber, Early, Late blights of Tomato were significantly reduced at all treatments either alone or in combinations comparing with untreated plants. Application with either B. subtilis-26D and B.subtilis-M22showed significant reduction in diseases incidence comparing with the untreated control. Journal of agricultural sciences №15 (02): 134-137, 2015